사상 체질별 음성과 건강 수준 관련 가능성에 대한 고찰 - 유현희(Hyunhee Ryu); 이시우(Siwoo Lee); 조태형(Tai-Hyoung Cho) (동의생리병리학회지, 2012)
In this work, we investigate the correlation between health condition and voice to study the validity and value of voice diagnosis. For this purpose, we collected voices, Health index questionnaires (Short form 36, Psychological Well Being Index) and Sasang Constitution informations on 197 males at the age of twenties. Pitch, jitter, shimmer variables were analyzed by ANOVA and Pearson correlation coefficient. There were no significant correlations between pitch, jitter, shimmer and health questionnaire score in total group regardless of Sasang Constitution. However, We found tendency of correlation between shimmer variables and health questionnaire scores in Taeeumin and Soyangin. In Soeumin and Soyangin, zitter and pitch variables were found to be slightly correlated with health questionnaire scores. Our study suggests the possibility that voice might be related with both health condition and Sasang Constitution. Our finding may motivate research activities towards diverse clinical applications of voice diagnosis and studies of voice characteristics in the Sasang constitution.